THE RELATIONSHIP BETWEEN TEACHER INTERPERSONAL BEHAVIOR AND STUDENT ENGAGEMENT AT AT SENIOR HIGH SCHOOL 5 PARIAMAN CITY - Airin Syafitri; Farah Aulia (Causalita, 2025)
In the learning process, students are individuals who must be actively involved physically, cognitively and emotionally. There are many factors that influence this involvement, one of which is the teacher's interpersonal behavior. This research aims to determine the relationship between teacher interpersonal behavior and student engagement at senior high school 5 Pariaman city. The sample in this study was selected using a stratified random sampling technique of 176 respondents. This research uses a quantitative correlational approach with Product Moment analysis techniques The results of the research identified that there is a relationship between teacher interpersonal behavior and student engagement at senior high school 5 Pariaman city with a coefficient correlation value of 0.538 > 0.05 (p > 0.05) on teacher interpersonal behavior (positive dimension), while there is a correlation coefficient value of -0.268 > 0.05 (p > 0.05) on behavior. teacher interpersonal (negative dimension). It can be concluded that there is a positive relationship between teacher interpersonal behavior (positive dimension) and student engagement at senior high school 5 Pariaman city, and there is a negative relationship between teacher interpersonal behavior (negative dimension) and student engagement at senior high school 5 Pariaman city.